Analisis Pengaruh PDB Iran, Kurs Dolar AS dan Inflasi Indonesia terhadap Nilai Ekspor Indonesia ke Iran Periode 2006.1-2017.4 - Diautoriq Husain; Bambang Sulistyono; Didit Welly Udjianto; Purkon Hidayat (Jurnal ICMES, 2021)
During 2003-2017, the government continued to strive to increase the value of its exports, one of which was by opening alternative markets as broad as possible. This effort aims to minimize risk amid global uncertainty. Iran then became one of the alternative market options that Indonesia could choose to increase its exports if it mirrored Indonesia's exports to Iran during 2003-2017. This research uses quantitative analysis. In looking at the effect of Iranian GDP, US dollar exchange rate, and Indonesian inflation on the value of Indonesia's exports to Iran quarterly over the period 2006.1-2017.4, this study uses Ordinary Least Square (OLS) multiple linear regression analysis because the data in time series form. This study indicates that Iranian GDP, US dollar exchange rate, and Indonesian inflation simultaneously have a significant effect on the value of Indonesia's exports to Iran. However, Iranian GDP partially has a positive and significant effect, and the US dollar exchange rate has a significant and negative effect, while Indonesian inflation has no effect.